Continuous biohydrogen production from poplar biomass hydrolysate by a defined bacterial mixture immobilized on lignocellulosic materials under non-sterile conditions. (10th March 2021) - Patel, Sanjay K.S.; Gupta, Rahul K.; Das, Devashish; Lee, Jung-Kul; Kalia, Vipin C.
Abstract: Lignocellulosic biowastes are rich in sugars and may be used as low-cost feed to produce environmentally friendly fuels such as hydrogen (H2 ). Poplar biomass is available in large quantities as a sugar-rich biowaste. Few studies have evaluated bacterial H2 production using well-defined mixed cultures (DMC) under non-sterile continuous culture conditions. DMC composed of high H2 -producing bacteria may circumvent the potential risk of a single bacterial culture being out-competed under non-sterile conditions. The novelty of this study lies in the continuous production of H2 from poplar biomass using DMC in immobilized state under non-sterile conditions. Under optimized continuous culture conditions with DMC immobilized on coconut coir, a H2 yield of 2.83 mol/mol of hexose was steadily obtained over a period of 40 days, which was four-fold higher compared to that obtained with Bacillus thuringiensis . This approach may enable to meet the increasing demand for cleaner energy-rich fuels on a large-scale in a steady manner. Highlights: Hydrogen production from poplar biomass under non-sterile conditions. Six-fold higher hydrogen yield through defined mixed cultures. Four-fold higher hydrogen using immobilized bacteria under continuous culture. Continuous hydrogen production for 40 days under non-sterile conditions.